The Impact of Posttraumatic Stress Disorder on CPAP Adherence in Patients with Obstructive Sleep Apnea - Collen, Jacob F. (American Academy of Sleep Medicine, 2012)
INTRODUCTION: Obstructive sleep apnea (OSA) is a common comorbid condition in patients with posttraumatic stress disorder (PTSD); insufficiently treated OSA may adversely impact outcomes. Sleep fragmentation and insomnia are common in PTSD and may impair CPAP adherence. We sought to determine the impact of combat-related PTSD on CPAP adherence in soldiers. METHODS: Retrospective case-control study. Objective measures of CPAP use were compared between OSA patients with and without PTSD. Groups were matched for age, BMI, and apnea-hypopnea index (AHI). RESULTS: We included 90 patients (45 Control, 45 PTSD). Among the cohort, mean age was 39.9 ± 11.2, mean BMI 27.9 ± 8.0, mean ESS 13.6 ± 5.7, and mean AHI 28.2 ± 22.4. There was a trend towards a higher rate of comorbid insomnia among patients with PTSD (25.8% vs. 11.1%, p = 0.10). PTSD was associated with significantly less use of CPAP. Specifically, CPAP was used on 61.4% ± 22.2% of nights in PTSD patients compared with 76.8% ± 16.4% in patients without PTSD (p = 0.001). Mean nightly use of CPAP was 3.4 ± 1.2 h in the PTSD group compared with 4.7 ± 2.2 h among controls (p < 0.001). Regular use of CPAP (> 4 h per night for > 70% of nights) was also lower among PTSD patients (25.2% vs. 58.3%, p = 0.01). CONCLUSION: Among soldiers with OSA, comorbid PTSD was associated with significantly decreased CPAP adherence. Given the potential for adverse clinical outcomes, resolution of poor sleep quality should be prioritized in the treatment of PTSD and potential barriers to CPAP adherence should be overcome in patients with comorbid OSA. CITATION: Collen JF; Lettieri CJ; Hoffman M. The impact of posttraumatic stress disorder on CPAP adherence in patients with obstructive sleep apnea. J Clin Sleep Med 2012;8(6):667-672.